The Influence Of Arabic Literature And Jurisprudence In A Contemporary Period And Sustainable Development - Achara, Issah Zubairu (Civilization Research: Journal of Islamic Studies, 2025)
This paper titled “The influence of Arabic literature and jurisprudence in a contemporary period” shall focus on Arabic literature and his influence, Arabic literature has been categorized into two categories, prose and poetry. On the other hand it has been categorized into different categories; we have Arabic literature in pre-Islamic era, with promise poets like Imru-kais, Antara bn shidad, Zuhair bn Abi Salm and Labied etc. Arabic literature in Islamic period with prominent poets like Khansa, Hassan Bn Thabiti. The aims and objectives of this article is to create an awareness  to the society about the significance of Arabic literature and jurisprudence, to encourage students to put more efforts in them to know about Arabic literature and jurisprudence in the area of their studies and to create an awareness to the community about the relevance of  Arabic literature and jurisprudence in contemporary period The problem of this paper is that many people or students are running away from Arabic literature and Jurisprudence, people don’t want to read Arabic literature because of poetry, Jurist also help us to understand Islamic law which enables us to understand about Shariah-law. Finding people are not ready to practice Shariah law in Nigeria suggestions and recommendations is that Nigerian government should try and enact Shariah law so that Muslims should be able to practice their Shariah law accordingly. Finally, the researcher used an analytical methodology.